PENGAWASAN KARYAWAN LAUNDRY SECTION DI TJOKRO HOTEL PEKANBARU - Rinda "; Mariaty " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Employees of the laundry section are an important part of a hotel that deals directly with guest service and comfort regarding linen cleanliness. This study aims to determine how the controling of employees and to find out the constraints that affect the performance of these employees. Employees of the laundry section at Tjokro Hotel Pekanbaru Using qualitative descriptive methods, researchers interviewed 5 respondents. Data collection techniques in this study used observation, interviews and documentation. the results of the research that has been done so far the employee performance is quite good even though it has several obstacles that affect employee performance. Keywords: employee controling, laundry section, constraints, Tjokro Hotel Pekanbaru.